Environment as a Legal Subject in the Reconstruction of Indonesia’s Environmental Law - Fernando, Zico Junius; Sinaga, Lestari; Iskandar, Iskandar; Mardin, Nurhayati; Arifin, Firdaus (Indonesian Journal of Environmental Law and Sustainable Development, 2025)
This study aims to analyze the new paradigm of recognizing the environment as a legal subject within Indonesia's legal system and its implications for environmental law enforcement. Driven by the increasingly complex environmental crisis caused by natural resource exploitation, environmental degradation, and climate change, this paradigm introduces an eco-centric approach and the theory of biocentric justice. The concept acknowledges the environment as a legal entity with intrinsic rights to exist, develop, and be restored when damaged. The research employs a normative approach with qualitative analysis methods and comparative studies of countries such as Ecuador, Bolivia, New Zealand and India which have implemented the recognition of the environment as a legal subject. The findings indicate that recognizing the environment as a legal subject in Indonesia requires comprehensive legal reforms, including constitutional amendments, the enactment of specific laws on environmental rights, strengthening law enforcement institutions, and empowering communities. This recognition is expected to enhance environmental law enforcement, establish ecological justice, and promote sustainable development. Therefore, this paradigm not only serves as a solution to the environmental crisis but also reflects Indonesia's commitment to Pancasila values and the sustainability of future generations.